Development of a SYBR Green real-time PCR-based assay system for detection of Neisseria gonorrhoeae - Andi Yasmon; Rela Febriani; Louisa Ivana Utami; Fithriyah Fithriyah; Yeva Rosana; Fera Ibrahim; Pratiwi Sudarmono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2022)
Diagnosis of Neisseria gonorrhoeae infection is needed for patient therapy and for reducing this bacterial transmission in the population. The culture method is a gold standard method for N. gonorrhoeae detection, however it has low sensitivity. Among molecular methods with high sensitivity and specificity, SYBR Green real-time PCR is the potential method for N. gonorrhoeae detection. In this study, we developed an SYBR Green real-time PCR-based system assay for N. gonorrhoeae detection. Several PCR conditions were optimized and analyzed including primer annealing temperature, DNA template volume, the limit of detection (LoD), cross-reaction with others (bacteria, viruses, fungus, protozoa), and quality assurance. The results showed that the annealing temperature and DNA template volume were 60oC and 5 µL, respectively. The LoD was 29 DNA copies corresponding to 3 bacterial cells per reaction. No cross-reaction was detected for other bacteria, viruses, fungus and protozoa. The external quality assurances enrolled in 2019 and 2021 showed 100% concordance. The preliminary testing for clinical samples was also 100% concordance. In conclusion, the SYBR Green real-time PCR-based system assay developed in this study is promising for application in clinical laboratories.